The complex interplay between vitamin D deficiency and diabetes - Tomasello, Giovanni; Sinagra, Emanuele; Raimondo, Dario; Cappello, Francesco; Damiano, Giuseppe; Palumbo, Vincenzo Davide; Cammà, Calogero; Macaluso, Fabio Salvatore; Genco, Chiara; Ciofalo, Marco; Raineri, Anna; Incandela, Maria; et al. (Progress in Nutrition, 2014)
It has been recently highlighted the link between vitamin D and metabolic and immunological processes, which established its role as an essential component of human health preservation. Vitamin D has been defined as natural immune modulators, and through the activation of its receptors (VDRs), it regulates calcium metabolism, cellular growth, proliferation and apoptosis, and other immunological functions. In this setting, vitamin D has also been reported to influence glucose regulation via effects on insulin secretion and action. Vitamin D deficiency is strongly associated with obesity mostly due to the storage of vitamin D in adipose tissue because of its lipophilic properties. The decrease in vitamin D levels may occur through several mechanisms such as a decrease in the calcium concentration, an increase in PTH, or a direct effect of vitamin D on worsening insulin resistance and secretion, augmenting the risk of developing type 2 diabetes. On the other hand, retrospective analysis and observational studies demonstrated high prevalence of vitamin D deficiency in patients with type 1 diabetes  and suggested a contributory role in the pathogenesis of type 1 diabetes, specially with certain allelic variations of the VDR.  Vitamin D supplementation during pregnancy and early childhood decreased the risk of autoimmune diabetes and perhaps, even after the onset of diabetes, it may improve glycemic control. In addition, in subjects that are affected by a high risk of developing diabetes (impaired fasting glucose and/or glucose tolerance, possibly without obesity) vitamin D supplementation could be helpful on the prevention of type 2 diabetes.